2013
DOI: 10.1136/jech-2012-202336
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of haemoglobin levels of African women are less important in areas with more health facilities: a multilevel analysis

Abstract: Interventions aimed at improving the Hb level of African women should take socioeconomic and contextual aspects into account. Increasing availability of health facilities might be a tool for reducing socioeconomic differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
12
1
1
Order By: Relevance
“…This is consistent with the study of Haverkate et al, (2014). They have considered land ownership as one of the measures of wealth.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the study of Haverkate et al, (2014). They have considered land ownership as one of the measures of wealth.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown inverse relationships between BMI and anemia [31, 32, 34, 42]. A multi-country, multi-level analysis of hemoglobin levels of African women showed stronger associations of anemia with socioeconomic and contextual factors than with BMI [11]. Micronutrient deficiencies have been shown to have different roles in etiology of varying severities of anemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published studies on anemia in SSA focus on children and pregnant women [4–9]. Men and elderly populations have received relatively little attention [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Many studies do report travel time, distance, or health facility population coverage as significant factors in adequate ANC attendance[ 49 , 55 57 ]. Haverkate et al’s analysis of women’s hemoglobin status found that hemoglobin differences due to wealth quintiles were attenuated by increased number of health facilities[ 60 ]. In our analyses, HSC capacity, access, and supply factors were not associated with any IFA receipt, regardless of whether ANC variables were included in the model or not.…”
Section: Discussionmentioning
confidence: 99%